PENINGKATAN KETERAMPILAN MENYUSUN TEKS CERITA SEJARAH MENGGUNAKAN STRATEGI GENIUS LEARNING MATA PELAJARAN BAHASA INDONESIA PADA KELAS XII BAHASA 1 DI SMAN 2 MAUMERE - AGUSTINA YUVENTA (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2020)
This study aims to improve the skills of composing the history stories of students of class XII Language 1 of SMA Negeri 2 Maumere by implementing a genius learning strategy. Through the genius learning model, improvement can be seen both in processes and products. The research subjects subjected to action were students of XII Language 1 of SMA Negeri 2 Maumere, totaling 29 students. The research model used is Classroom Action Research (CAR). The procedure for implementing the action and implementing the action at the study site is divided into two cycles. Each cycle is done three times. This research is focused on issues related to improving the skills of composing Historical Story Texts by applying genius learning strategies. The data analysis technique was carried out using qualitative and quantitative description techniques. The criteria for success achieved by students in this study is seen from a change in the direction of a better and increased learning and the results in the practice of composing Story Text. The results of the study show the following. First, the use of genius learning strategies can improve the quality of the learning process of composing historical narrative texts. An increase in the process in aspects of the learning situation, student focus and activeness, makes positive changes so that learning makes composing historical narrative texts more interesting and enjoyable. Second, learning to compose Historical Story Texts with a genius learning strategy can improve the results of the skills of composing historical story texts. This can be seen from the average score of the skills to compose the historical story text in cycle I was 64.53 whereas after being given the action of the second cycle the average score was 85.00. This shows an increase of 20.47. Overall, at the end of the second cycle, all aspects and criteria for composing historical narrative texts experienced a significant increase. Based on the results of the research above, it is known that the use of genius learning strategies is successful and can improve the skills of compiling the history story text of students of class XII Language 1 of SMA Negeri 2 Maumere.